PERENCANAAN JALAN INSPEKSI DARI TERMINAL EKSISTING KE TERMINAL BARU DI SISI TIMUR RUNWAY 31 BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Jesida Alfiyana; Djoko Priambodo; Oka Fatra (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The condition of the inspection road at Ahmad Yani International Airport Semarang currently only has inspection roads on the west side of runway 13 with an inadequate width of road to be passed by inspection vehicles and the absence of inspection roads in the east side of the runway 31. New road inspection planning is needed on the east side of runway 31 using a flexible pavement type with Component Analysis calculation method and geometric planning of the road using the rules for the Procedure for Inter-City Road Geometric Planning No.038 / TBM / 1997. From the results of the calculation analysis, the thickness of the road for the age of 10 years 34.125cm with surface layer 4.125cm, basecourse layer 20cm and subbase layer 10cm. The thickness of the planned 20 year old road 35.50cm with a layer surface 5.5cm, the basecourse layer 20cm and the subbase layer 10cm. The plan speed is 60km/h, the road length is 1903m and the road width is 2 x 2.75m (5.5m) consisting of 2 2-way lanes. Transverse slope of 2%, road shoulder 3% and width of drainage channel 0.5m. For the results of road geometric planning, the road inspection conditions at Ahmad Yani International Airport Semarang currently only have inspection roads on the west side of runway 13 with 5 bends with Spiral - Spiral and Spiral - Circle - Spiral types with widening at each bend of 3.17m.